1972
DOI: 10.1007/bf01219980
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dimethylbiguanide (metformin�) on carbohydrate metabolism in obese, non-diabetic women

Abstract: The authors have studied the influence of 2 weeks' treatment of 15 non-diabetic, obese subjects with 2 g of Metformin daily, on intravenous glucose tolerance and plasma insulin levels. Blood glucose fasting and during the IVGTT were not influenced by treatment, but the insulin levels and the insulin/glucose ratios were significantly decreased. This points to a decreased insulin resistance. Influence du traitement d la Metformine sur le mgtabolisme glucidique chez des femmes ob~ses non diabdtiques Rdsumd. Les a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Intriguingly, previous observational studies have shown reduced mortality of type II diabetic patients taking metformin during COVID-19 (Crouse et al, 2020). The aim to improve the effect of metformin led to the development of phenformin (Sterne, 1963), which showed an improved cellular uptake compared to metformin (Sogame et al, 2009). We hence decided to use phenformin for experimental validation of our approach.…”
Section: Identification Of Drug Targets For Broad-spectrum Antiviral ...mentioning
confidence: 99%
“…Intriguingly, previous observational studies have shown reduced mortality of type II diabetic patients taking metformin during COVID-19 (Crouse et al, 2020). The aim to improve the effect of metformin led to the development of phenformin (Sterne, 1963), which showed an improved cellular uptake compared to metformin (Sogame et al, 2009). We hence decided to use phenformin for experimental validation of our approach.…”
Section: Identification Of Drug Targets For Broad-spectrum Antiviral ...mentioning
confidence: 99%